The importance of work organization on workload and musculoskeletal health – Grocery store work as a model. (March 2016) - Balogh, I.; Ohlsson, K.; Nordander, C.; Björk, J.; Hansson, G.-Å.
Abstract: We have evaluated the consequences of work organization on musculoskeletal health. Using a postal questionnaire, answered by 1600 female grocery store workers, their main work tasks were identified and four work groups were defined (cashier, picking, and delicatessen work, and a mixed group, who performed a mix of these tasks). The crude odds ratios (ORs) for neck/shoulder complaints were 1.5 (95% CI 1.0–2.2), 1.1 (0.7–1.5) and 1.6 (1.1–2.3), respectively, compared to mixed work. Adjusting for individual and psychosocial factors had no effect on these ORs. For elbows/hands, no significant differences were found. Technical measurements of the workload showed large differences between the work groups. Picking work was the most strenuous, while cashier work showed low loads. Quantitative measures of variation revealed for mixed work high between minutes variation and the highest between/within minutes variation. Combining work tasks with different physical exposure levels increases the variation and may reduce the risk of musculoskeletal complaints. Highlights: Physical workload and musculoskeletal symptoms in grocery store workers are clarified. Single work tasks had higher risk for musculoskeletal complaints than mixed one. Cashiers had lowest physical loads but highest musculoskeletal complaints. The low variation for cashiers might explain high risk for neck/shoulder complaints. Combining work tasks with different workloads will improve the work situation.